Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Consider commutative semigroup S and its Grothendieck completion group G(S).Suppose I insist on defining G(S) as free abelian group on basis $[a]$ (with $a\in S$) divided out by the relations $[a+b]-[a]-[b]$. How do I show with that definition that if the images of $a,b\in S$ become equal in G(S), then necessarily there existed $c\in S$ with a+c=b+c ? I know it true because I can prove it with other construction of grothendieck group, but I should like direct proof with above free abelian group construction.

share|cite|improve this question
up vote 10 down vote accepted

Well your notation is a little bit confusing. Since we are considering free abelian groups, we should avoid additive notations for the commutative semigroup S. Let's talk of $(S, \ast )$. If $F(S)$ is the free abelian group with basis $S$, we can assume $S \subseteq F(S)$. So the set of relations is $$R = \{ (a \ast b) -a - b : a,b \in S \}.$$ Then, the Grothendieck completion is the abelian group $$G(S) = F(S)/ \langle R \rangle.$$ If $a \in S$, I'll denote the coset $a + \langle R \rangle$ by $[a]$.

The proof isn't hard. You'll just need to remember that in free abelian groups the expression in terms of a basis is unique. You can find one proof, with an ugly notation, in Rotman's 'Advanced Modern Algebra'. I'll reproduce below the proof on Magum's book 'An Algebraic Introduction to K-theory'.

Suppose that $[a]=[b]$. Then, $a-b \in \langle R \rangle$. That is, $$a-b = \sum_{i=1}^n n_i((a_i \ast b_i) - a_i - b_i),$$ where $n_i = 1$ or $-1$ and $a_i, b_i \in S$. Bringing terms with negative coefficients to the other side, $$ a + \sum_{n_i = -1}(a_i \ast b_i) + \sum_{n_i = 1}(a_i + b_i) = b + \sum_{n_i = 1}(a_i \ast b_i) + \sum_{n_i = -1}(a_i + b_i).$$ Since $S$ is a basis of $F(S)$, the terms on one side of the equation are a permutation of those on the other side. Since $(S, \ast )$ is commutative, it follow that, in S, $$ a \ast \prod_{n_i = -1}(a_i \ast b_i) \ast \prod_{n_i = 1}(a_i \ast b_i) = b \ast \prod_{n_i = 1}(a_i \ast b_i) \ast \prod_{n_i = -1}(a_i \ast b_i). $$ So $a \ast c = b \ast c$, where $$ c = \prod_{i = 1}^n (a_i \ast b_i).$$

share|cite|improve this answer
Thank you for this very clearly and precisely written answer. – evgeniamerkulova Oct 25 '10 at 7:41
@Evgenia: I'm glad you like it. – Nuno Oct 25 '10 at 20:18

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.